Predictors of Coronary Heart Disease (CHD) among Malaysian Adults: Findings from MyDiet-CHD Study - Wan Musa, Wan Zulaika; Ahmad, Aryati; Abu Bakar, Nur Ain Fatinah; Wan-Arfah, Nadiah; Ramli, Ahmad Wazi; Naing, Nyi Nyi (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: This study aimed to determine the risk factors of CHD among the Malaysian adult population. Methods: Using a cross- sectional observational study design, this study involved 365 adult patients aged between 30-64 years, attending clinics from eight government hospitals and four health clinics in Terengganu, Pahang, Selangor, Putrajaya, Penang, Kedah, Johor and Sabah from February 2018 until September 2020. Sociodemographic characteristics, clinical and dietary data, physical activity and stress level were recorded using a structured questionnaire. Multiple logistic regression was used to analyse CHD risk factors. Results: The overall response rate was 99.2%. The adjusted odds ratio of CHD was greater for age (AOR; [%95 CI]) (1.043;[ 1.009,1.078]); waist circumference (1.033;[1.009, 1.057]); total fat intake (1.035;[1.021, 1.050]); full cream dairy products intake (1.004;[1.001, 1.008]); smokers vs non-smokers (4.691;[2.399, 9.176]); individual with family history of CHD vs without family history (2.705;[ 1.496, 4.891]); married vs single (0.434;[ 0.217,0.867]); and lower for HDL cholesterol (0.185;[0.052, 0.662]); Chinese vs Malays (10.619;[ 2.255, 49.995]); and third lowest income (0.197;[ 0.073, 0.532]) and forth lowest income (0.167;[ 0.056, 0.499]) vs lowest income. Conclusion: Age, race, income, smoking and marital status, family history of CHD, waist circumference, HDL cholesterol, total fat intake, full cream dairy products intake were significantly associated with CHD among this population. This finding is particularly important to the primary health carers to identify at-risk CHD individuals thus appropriate intervention could be provided.